Dampak Kemacetan Kopo Sayati Terhadap Manajemen Kecerdasan Emosional Pengenadra Berisiko - Fitri Khoerunnisa; Ageng Saepudin Kanda (Journal of Management and Social Sciences, 2024)
Kopo Sayati, more precisely Miko Mall Bandung, is one of the traffic jam points in the city of Bandung, West Java. From these problems, each individual with a different character, as a driver, must have their own point of view in overcoming the problem. The impact that arises must vary according to their respective nature, behavior, and personal character. The purpose of this study is to open the mind and process the EQ (emotional intelligence) of each driver so that they drive properly, not harming themselves or others. Traffic jams have an impact on emotional intelligence for motorists and are very reliable when they are stuck in these conditions. The methods used by these researchers are useful for achieving goals such as, facilitating connectivity and traffic accessibility, in addition to providing alternatives for citizens to increase economic productivity